Slobodna volja između filozofije i znanosti - Grgić, Filip, filozof (Array, 2019)
The paper discusses the status of widespread scientific views on free will among many contemporary scientists, especially the view that free will is an illusion,. It argues, firstly, that the problem of free will is a conceptual problem, in a very strict sense; secondly, that that which is standardly called “the problem of free will” is inseparable from the context within which it emerged, i.e., the philosophical attempt to solve the alleged conflict between freedom and determinism, and that outside this framework it has no meaning and thirdly, that the term “freedom” as it is used in philosophical and scientific claims also has no independent meaning outside this framework. It follows that, among other things, a definitive solution to the problem of free will is not possible, but that this need not be of particular import to people's lives.